Work–family conflict, overwork and mental health of female employees in China - Ma, Jun; Xu, Laixi; Zhang, Xuehe (Frontiers in Public Health, 2025)
IntroductionThe “Green Paper on the Mental Well-being of Chinese Career Women” indicates that around 85% of Career Women face mental health challenges such as anxiety, depression, and anger, with these issues being more common than in their male counterparts in China. Both work and family are identified as two major contributors to these problems. Utilizing Conservation of Resources theory, this paper examines work–family conflict and overwork as significant explanatory variables and develops a moderated mediation model to investigate the mechanisms affecting mental health issues among Chinese career women.MethodsData were gathered through a questionnaire survey, with 500 questionnaires distributed and 393 responses received. Hayes’ PROCESS macro for SPSS was employed to examine moderated mediation models, with Bootstrap resampling set at 1000.Results(1) Work–family conflict (abbreviated as WFC) is significantly associated with emotional exhaustion (abbreviated as EE) and mental health problems in career women, with emotional exhaustion serving as a mediator between work–family conflict and mental health. (2) Overwork is positively linked to emotional exhaustion and influences the relationship between work–family conflict and emotional exhaustion. (3) Overwork also moderates the mediation effect of work–family conflict on mental health via emotional exhaustion, amplifying the mediation effect when career women are overburdened.DiscussionThis study provides fresh insights into the mechanisms underlying mental health issues among career women, offering valuable information for addressing these challenges.